Reclaiming Indigenous Research in Higher Education - Brayboy, Bryan McKinley; Shotton, Heather J., 1976-; Minthorn, Robin Starr (Book collections on Project MUSE., 2018)
This book highlights the current scholarship emerging from Native American scholars in higher education. From understanding how Indigenous students make their way through school, to tracking tribal college and university transfer students, this book allows Native scholars to take center stage, and shines the light squarely on those least represented among us.